Successful Management of Third Eyelid Tumor by Chemo Reduction and Surgical Therapy in a Chippiparai Dog - N. Krishnaveni; E. Kalaiselvan; Anubharathi; K. Thangadurai; A.R.Ninu; K. Gopal; M.Madeena Begum (The Indian Veterinary Journal, 2025)
Three years old female Chippiparai dog was reported with the history of having a reddish growth on the medial canthus of left eye for 20 days. Ophthalmic examination revealed soft friable reddish nodular lesion on the palpebral surface of the left third eyelid. Cytology of the biopsy sample revealed squamous cell carcinoma (SCC). In the presented case, Chemoreduction with topical Mitomycin C followed by surgical resection of the residual tumor with wide surgical margin resulted in successful management of the third eyelid tumor with no recurrence.